Pengaruh Pemahaman Peraturan Perpajakan, Kesadaran Wajib Pajak Dan Sanksi Pajak Terhadap Tingkat Kepatuhan Wajib Pajak Profesi Dokter Di Bandar Lampung - Andara, Ginta Roka; Andriyanto, R. Weddie; Sumanda, Kamadie (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research aims to determine the effect of understanding tax regulations, taxpayer awareness, tax rates, and tax sanctions on the level of taxpayer compliance among doctors in Bandar Lampung. This type of research is quantitative descriptive research. The data collection technique used in the research was a questionnaire. The population used in this study were all doctors in Bandar Lampung. Based on the Slovin formula, the number of samples used in this research is 264 samples of taxpayers who work as doctors. Hypothesis testing in this research was carried out using multiple linear regression analysis techniques. The results of the research show that understanding tax regulations, taxpayer awareness, tax rates and tax sanctions have a significant effect on the level of taxpayer compliance for the medical profession in Bandar Lampung.